The effectiveness of the "Mato-Oput 5" curriculum in changing school children's attitudes towards conflict and violence, and in reducing pupil perpetrated acts of violence - Mutto, Milton (My University, 2007)
Objectives The study evaluated the effectiveness of the “Mato-Oput 5” curriculum in changing children’s attitudes towards conflict and violence and preventing violent acts by them; specifically, it determined attitudes differences between children exposed to and those not exposed to the intervention, and compared rates and trends of pupil-perpetrated intentional (violent) and severe intentional incidents among the children who were taught and those were not taught the curriculum. Methods and setting The study was analysis of secondary data from a community trial. The original study had been conducted in a war affected rural district in Northern Uganda in 2002. Results The intervention and control groups had comparable demographic characteristics, attitudes towards conflicts and violence, and rates of intentional and severe intentional incidents (violence) before intervention. After intervention, they remained comparable with regard to their demographic characteristics and rates and trends of intentional and severe intentional incidents. Their attitudes towards conflicts and violence, however, differed significantly, with the intervention group tending towards forgiving of offenders, and away from forceful response to provocation more than the control group. Both groups had post-intervention rate reductions in intentional incidents, and rate increments in severe intentional incidents. The pre-intervention incident rates in the intervention and control groups were 270/1000 and 370/1000 respectively, while the post-intervention rates were 190/1000 and 350/1000 respectively. Before intervention, seven in every 1000 incidents in the intervention group required school first aid or treatment in a health facility (severe incidents) as compared to 12 in every 1000 in the control group. These rates increased to 150/1000 and 160/1000 respectively after intervention. Conclusions The Mato-Oput 5 curriculum was effective in changing children’s attitudes towards conflict and violence: the intervention group tended towards forgiveness of offenders and non-forceful responses to provocation more than the control group. The rates and trends of pupil-perpetrated intentional (violent) and severe intentional incidents in the two groups of children, however, remained comparable.
Student Number : 0417597W - MSc(Med) research report - School of Public Health - Faculty of Health Sciences
Keywords: “Mato-Oput 5” curriculum; conflict; violence; attitudes differences; Northern Uganda; demographic characteristics